Strengthening climate change adaptation capacity in Africa- case studies from six major African cities and policy implications - Filho, W.L. (Elsevier Ltd, 2018)
Africa is one of the most vulnerable regions in respect of climate change. As the African continent struggles to adapt to climate change, a variety of measures are being pursued to alleviate the resultant pressures on people, properties and their livelihoods in several African cities. Collectively, they show that climate change adaptation in Africa is not as hopeless as widely claimed, and that there are some promising prospects. The literature shows a deficiency on studies which examine the extent to which climate change adaptation is being pursued in African cities. This paper addresses this need, and outlines some of the most important climate threats (e.g. increasing temperatures, droughts, sea level rise, sea and river flooding) and synergic non-climate factors, as well as recent progress made in respect of implementing climate change adaptation in African cities. Rather than adopt a general description of trends, this research focuses on concrete case studies from six major cities across the central, western, and eastern regions of the African continent (Douala, Lagos City, Dar-es-Salaam, Accra, Addis Ababa and Mombasa). The vulnerability and adaptive capacity status of the studied cities are discussed. Difficulties and challenges encountered in implementing adaptation policies in these areas are also highlighted. Furthermore, some successful examples of climate change adaptation initiatives in the surveyed cities are provided. Finally, the paper outlines some of the policy measures which can be implemented towards strengthening the capacity of African cities to adapt to a changing climate. Â© 2018 Elsevier Ltd